Numerical Analysis Of Flexible Pavement On Soft Soil Using Finite Element Method - Yonas Prima Arga Rumbyarso (Universitas Islam Sultan Agung, 2025)
Road he construction of flexible pavement on soft clay subgrades faces challenges due to low bearing capacity, high compressibility, and sensitivity to moisture. This study analyzes the stress–strain response of soft clay using Finite Element Method with three water content scenarios: 19%, 36%, and 53%. The 2D model consisted of a 57 cm clay layer and a 3 cm pavement layer, with soil parameters obtained from laboratory tests and represented by the Mohr-Coulomb model. The results show that effective stress increased slightly with higher water content, from 10.57 kN/m² at 19% to 11.54 kN/m² at 53%. In contrast, displacement remained nearly constant at around 0.2046 mm. This indicates that while moisture variation affects stress distribution, it has minimal impact on soil deformation under the modeled conditions. These findings suggest that flexible pavement on soft clay may maintain stable deformation despite increased moisture, providing useful insights for pavement design on problematic soils.